Ekspektasi Komunitas Kamera Nikon: Brand Personality dalam Mempertahankan Brand Loyalty - Renata, Natasha (Business Education Program of Universitas Pendidikan Indonesia, 2019)
Â Abstract: The purpose of the research is to find out the influence of brand personality on brand loyalty. The object becomes the unit of analysis in this research is camera Nikon community Indonesia. The type of research is using descriptive with the explanatory method survey of 106 respondents. The results of Â this research indicate that the brand personality in the good category and brand loyalty in the good category. In this research findings if the conditions of the brand personality is good, then it will increase brand loyalty.